Pulse pressure amplification and cardiac autonomic dysfunction in patients with type 2 diabetes mellitus. (September 2018) - Eleftheriadou, Ioanna; Drosos, George; Tentolouris, Anastasios; Konstantonis, Giorgios; Sfikakis, Petros; Protogerou, Athanasios; Tentolouris, Nikolaos
Abstract The main aim of this cross-sectional study was to investigate the association between pulse pressure amplification (PPA) and cardiac autonomic activity (baroreflex sensitivity (BRS) and heart rate variability (HRV)) in patients with type 2 diabetes mellitus (T2DM). In addition, we examined the association between cardiac autonomic activity and central hemodynamic parameters that may affect PPA such as augmentation index (AIx), aortic stiffness (pulse wave velocity (PWV)), and common carotid artery stiffness distensibility coefficient (DC). A total of 142 patients with T2DM were included in the study. In multivariate linear regression analysis—after controlling for age, diabetes duration, height, waist circumference, aortic PWV, use of β-blockers, and BRS—PPA was associated significantly and independently with male gender (standardized regression coefficient (β ) = 0.156, p = 0.007), aortic systolic blood pressure (β = −0.221, p < 0.001), heart rate (β = 0.521, p < 0.001), AΙx (β = −0.443, p < 0.001), and parameters of HRV, such as total power of HRV (β = −0.157, p = 0.005). No significant associations were found between BRS or parameters of HRV with aortic PWV, AIx, or DC. In patients with T2DM, cardiac autonomic dysfunction was associated with enhanced PPA. This association was independent from the well-described effect of resting heart rate, as well as from traditional cardiovascular risk factors or diabetes-related factors. Moreover, it was not mediated by effects of the autonomic dysfunction on arterial stiffness or on pressure wave reflections. These findings suggest that cardiac autonomic dysfunction affects PPA by mechanisms other than resting tachycardia and arterial properties.